2016
DOI: 10.2147/vhrm.s109032
|View full text |Cite
|
Sign up to set email alerts
|

A stress-related explanation to the increased blood pressure and its course following ischemic stroke

Abstract: BackgroundA hypertensive response after ischemic stroke is frequent, yet its pathophysiology is unknown. Mechanisms related to local ischemic damage, major vascular occlusion, and psychological stress due to acute illness have been proposed. We assessed the natural course of blood pressure (BP) within the first 24 h in groups of ischemic stroke patients with different characteristics. We hypothesized that a consistent BP reduction, regardless of stroke location, time window from debut to admission and presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Risk factors for sICH after thrombolysis such as stroke severity, onset-to-treatment time, and early signs of infarction on CT may reflect the extent and progression of ischemic injury to the blood–brain barrier. Other risk factors such as stroke-associated hyperglycemia and hypertension may represent an acute stroke-related stress reaction ( 24 , 25 ), and there is debate whether stroke-associated hyperglycemia is merely an epiphenomenon (and a marker) or a cause of poor outcome and sICH ( 22 , 26 ). In contrast to these risk factors, the novel candidate risk factor pretreatment with statins may contribute to a higher risk of clinically relevant hemorrhage after rt-PA via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for sICH after thrombolysis such as stroke severity, onset-to-treatment time, and early signs of infarction on CT may reflect the extent and progression of ischemic injury to the blood–brain barrier. Other risk factors such as stroke-associated hyperglycemia and hypertension may represent an acute stroke-related stress reaction ( 24 , 25 ), and there is debate whether stroke-associated hyperglycemia is merely an epiphenomenon (and a marker) or a cause of poor outcome and sICH ( 22 , 26 ). In contrast to these risk factors, the novel candidate risk factor pretreatment with statins may contribute to a higher risk of clinically relevant hemorrhage after rt-PA via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Because thrombotic or embolic occlusion is the reason for acute ischemic stroke, it might be the first trigger point leading to high blood pressure. Kvistad et al [15] found that, independent from the stroke subtype and proximal vessel occlusion, hypertensive patients (n = 1067) who were admitted with the complaint of acute stroke within the first 6 hours or later showed a significant decrease in blood pressure in the 24th hour after their admission. The reason for this finding might be because of psychological stress or white coat hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no relationship was found between high admission blood pressure and proximal vessel occlusion, which is consistent with Kvistad et al's study. [15]…”
Section: Discussionmentioning
confidence: 99%
“…Lacunar infarct (LACI), a small deep infarct that results from occlusion of a penetrating artery, accounts for approximately one-quarter of all ischemic strokes [ 1 ]. The corresponding lesion in the brain issue is removed to ultimately form a small cavity with a diameter of no more than 20 mm, although the majority of which are 2 to 4 mm.…”
Section: Introductionmentioning
confidence: 99%